The relationship between Scio-demographic Characteristics and the Application of Self Care Instruction Program for Patients with Double Lumen Catheter - Salam Salah Flayyih, Widad K Mohammed, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: to identify the influence of Socio-demographic Characteristics in the Application of Self Care Instruction Program for Patients with Double Lumen Catheter. Methodology: A quasi-experimental (non-randomized) design was used. Descriptive studies are conducted to describe the distribution of variables, provide information about health status, behavior, attitudes and characteristics of a specific population Conclusion: There a significant relationship between age and patients' knowledge pretest level, and also Showed significant relationships between knowledge of patients with their age and gender at the post-test level. Result: There was a significant relationship between age and patients knowledge pretest level at (P.value=.011), and also Showed significant relationships between knowledge of patients with their age at (P= .02) and gender at (P= .047) at the post -test level. Recommendations: Recommendations to Ministry of Health (Establishment of centers concerned with hemodialysis patients' rehabilitation, and Conducting specialized courses for medical and health staff concerned with the implementation of self-care programs for hemodialysis patients with double lumen catheters in hemodialysis units)